Application of Photosynthetic Bacteria and Chitosan on the Growth of Banana Lase (Musa acuminata L.) - Srilestari, Rina; Wijayani, Ari; Apriyanti, Dessy (Ridwan Institute, 2026)
The post-acclimatization stage is a critical period for Lase banana (Musa acuminata L.) plants derived from tissue culture, as they must adapt to open-field environmental conditions. The application of photosynthetic bacteria (PSB) and chitosan has the potential to enhance plant growth and development, as well as improve the tolerance of banana plants during the post-acclimatization stage. The primary objective of this study was to obtain Lase banana seedlings from tissue culture with optimal field growth through the application of PSB and chitosan. The experiment was conducted using a split-plot design in a field setting, with the main plots representing PSB concentrations (10, 20, and 30 mL/L) and the subplots representing chitosan concentrations (10, 15, and 20 mL/L). Data were analyzed using ANOVA at the 5% significance level and further tested using Duncan’s Multiple Range Test (DMRT) at the 5% level. The results showed a significant interaction between PSB at 20 mL/L and chitosan at 15 mL/L for several parameters, including root number and length, plant fresh weight, and total chlorophyll content of Lase banana plants.